Global social policy actors and factors in Indonesian social policy making - Alexandra Kaasch; Mulyadi Sumarto; Brooke Wilmsen (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper explores the transnational dimension of social policy by examining the case of Indonesia, where social policy systems have shifted from community-based schemes for social protection and targeting of the poor to more centralized but broadly national coverage. Focusing on the health care system in particular, it draws on in-depth elite interviews and relevant policy documents to demonstrate how global policy diffusion pushed Indonesia towards universal health care provision. It argues that global actors, such as AusAid, WHO and various UN agencies, played an important role in this transformation, and they have done so in different ways. It further argues that this was made possible by qualitative changes in the relationship between the Indonesian government and global actors, especially AusAid, that broke away from earlier models of foreign intervention.
Keywords: 330